Unlocking Synergistic Hepatoprotection: Dapagliflozin and Silymarin Combination Therapy Modulates Nuclear Erythroid 2-Related Factor 2/Heme Oxygenase-1 Pathway in Carbon Tetrachloride-Induced Hepatotoxicity in Wistar Rats - Shakta Mani Satyam; Laxminarayana Kurady Bairy; Abdul Rehman; Mohamed Attia; Layth Ahmed; Karam Emad; Yusuf Jaafer; Abdelrehman Bahaaeldin (Biology, 2024)
This study was aimed to investigate the hepatoprotective potential of dapagliflozin and silymarin alone and in combination to combat carbon tetrachloride (CCl4)-induced hepatotoxicity and the anticipated mechanisms. Thirty female Wistar rats were randomly allocated into five different groups. All the experimental animals except the normal control (Group I) were administered CCl4. Additionally, Groups II, III, IV, and V were treated with gum acacia, silymarin, dapagliflozin, and a combination of dapagliflozin and silymarin, respectively, for 14 days. Dapagliflozin, silymarin alone, and in combination, significantly reduced (p < 0.05) serum levels of ALT, AST, AST:ALT ratio, and total bilirubin compared to CCl4-intoxicated control rats. There was a notable reduction (p < 0.05) observed in the levels of IL-1beta, IL-6, TNF-alpha, nitrites, and 4-hydroxynonenal, accompanied by an elevation in catalase, superoxide dismutase, glutathione peroxidase, nuclear erythroid 2-related factor 2 (Nrf2), and heme oxygenase-1 (HO-1) in liver homogenates of the groups treated with dapagliflozin, silymarin alone, and in combination, as compared to the CCl4-intoxicated control group. Dapagliflozin in combination with silymarin showed a synergistic hepatoprotective effect. Our study reveals the profound hepatoprotective potential of dapagliflozin alone and in combination with silymarin in CCl4-intoxicated Wistar rats by modulating the Nrf2 and HO-1 signaling pathways.